A realist review of the causes of, and current interventions to address ‘missingness’ in health care - Lindsay, C; Baruffati, D; Mackenzie, M; Ellis, DA; Major, M; O'Donnell, K; Simpson, S; Williamson, A; Duddy, C; Wong, G (F1000Research, 2023)
Background This protocol describes a realist review exploring the problem of “missingness” in healthcare, defined as the repeated tendency not to take up offers of care that has a negative impact on the person and their life chances. More specifically, the review looks at the phenomenon of patients missing multiple appointments in primary care in the UK – at the causal factors that influence how patients come to be “missing” in this way, and what interventions might support uptake and “presence” in healthcare. Background research informing this project suggests that a high rate of missed appointments predicted high premature death rates, and patients were more likely to have multiple long-term health conditions and experience significant socioeconomic disadvantage. Most research in this field focuses on population- or service-level characteristics of patients who miss appointments, often making no distinction between causes of single missed appointments and of multiple missed appointments. There have therefore been no interventions for ‘missingness’, accounting for the complex life circumstances or common mechanisms that cause people to repeatedly miss appointments. Methods We use a realist review approach to explore what causes missingness - and what might prevent or address it - for whom, and in what circumstances. The review uses an iterative approach of database searching, citation-tracking and sourcing grey literature, with selected articles providing insight into the causal dynamics underpinning missed appointments and the interventions designed to address them. Discussion The findings of this review will be combined with the findings of a qualitative empirical study and the contributions of a Stakeholder Advisory Group (STAG) to inform the development of a programme theory that seeks to explain how missingness occurs, whom it affects and under what circumstances. This will be used to develop a complex intervention to address multiple missed appointments in primary care. PROSPERO registration CRD42022346006